How the Listener’s Attention Dynamically Switches Between Different Speakers During a Natural Conversation - Dai, Bohan; Zhai, Yu; Long, Yuhang; Lu, Chunming (Psychological science, 2024)
The neural mechanisms underpinning the dynamic switching of a listener’s attention between speakers are not well understood. Here we addressed this issue in a natural conversation involving 21 triadic adult groups. Results showed that when the listener’s attention dynamically switched between speakers, neural synchronization with the to-be-attended speaker was significantly enhanced, whereas that with the to-be-ignored speaker was significantly suppressed. Along with attention switching, semantic distances between sentences significantly increased in the to-be-ignored speech. Moreover, neural synchronization negatively correlated with the increase in semantic distance but not with acoustic change of the to-be-ignored speech. However, no difference in neural synchronization was found between the listener and the two speakers during the phase of sustained attention. These findings support the attenuation model of attention, indicating that both speech signals are processed beyond the basic physical level. Additionally, shifting attention imposes a cognitive burden, as demonstrated by the opposite fluctuations of interpersonal neural synchronization.